Adaptation and Validation of the Authoritative School Climate Survey in a Sample of Chilean Adolescents - Gálvez-Nieto, José Luis; Paredes, Francisco; Trizano-Hermosilla, Italo; Polanco-Levican, Karina; Tereucán-Angulo, Julio (Frontiers in Psychology, 2021)
Authoritative school climate is a relevant and novel construct that improves the academic performance and social-emotional development of students. This study aimed to evaluate the psychometric properties of reliability and validity of the Authoritative School Climate Survey in a sample of Chilean adolescents. A cross-sectional study was carried out, in which 808 students from 12 schools in Chile participated (55.1% men and 44.9% women), with a mean age of 15.94 (SD = 1.32). The results obtained through exploratory and confirmatory factor analyzes ratified the hypothesized structure of two correlated factors. As expected, evidence of criterion validity showed significant relationships between the measures of authoritative school climate and attitude towards institutional authority. This study provides evidence regarding the psychometric quality of the scale to assess authoritative school climate, allowing its use in the Chilean context.